2015
DOI: 10.1016/s0924-9338(15)30475-2
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Working Memory in Schizophrenia and Bipolar Disorder: the Effect of History of Psychotic Symptoms and Different Aspects of Cognitive Task Demands

Abstract: Comparisons of cognitive impairments between schizophrenia (SZ) and bipolar disorder (BPD) have produced mixed results. We applied different working memory (WM) measures (Digit Span Forward and Backward, Short-delay and Long-delay CPT-AX, N-back) to patients with SZ (n = 23), psychotic BPD (n = 19) and non-psychotic BPD (n = 24), as well as to healthy controls (HC) (n = 18) in order to compare the level of WM impairments across the groups. With respect to the less demanding WM measures (Digit Span Forward and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…In any case, there is broad agreement on the presence of an overlapping in the neurocognitive performance of both groups of patients in a way that the differences found are subtle [18]. On the other hand, also a number of studies have found the presence of differences in the working memory domain [12, 18, 6770], although the effect size is small. Interestingly, in our study, BD-NP did not differ from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, there is broad agreement on the presence of an overlapping in the neurocognitive performance of both groups of patients in a way that the differences found are subtle [18]. On the other hand, also a number of studies have found the presence of differences in the working memory domain [12, 18, 6770], although the effect size is small. Interestingly, in our study, BD-NP did not differ from the control group.…”
Section: Discussionmentioning
confidence: 99%